Research issues in safety performance: a literature review / Mohd Zaidi Mat Saat, Chandrakantan Subramaniam and Faridahwati Mohd Shamsudin - Mat Saat, Mohd Zaidi; Subramaniam, Chandrakantan; Mohd Shamsudin, Faridahwati (2016)
Safety performance has gained acceptance as a field of study and has been increasingly researched nowadays. Researchers and practitioners have attempted to investigate factors that influence safety performance which can improve the effectiveness and productivity of an organization. Nonetheless its importance, studies on safety performance have been limited and inadequate. More specifically, the literature review reveals that as a field of study, safety performance has received minimal focused on groups, organizational and industry level analysis instead of individual as well as in the context of Malaysian small and medium enterprises. Based on the review of the literature, this paper highlights some of the major issues and research areas on safety performance that require further investigation. Future research may attempt to identify environmental factors that influence safety performance